Prognostic significance of the pretreatment controlling nutritional status score in colorectal cancer patients: an updated meta-analysis with 24 cohort studies - Shang, Jingkun; Wei, Jinlai (Frontiers in Nutrition, 2025)
BackgroundThe prognostic significance of the Controlling Nutritional Status (CONUT) score in colorectal cancer has been extensively reported, yet it remains unclear. This study aims to conduct an updated meta-analysis to evaluate the association between pretreatment CONUT score and long-term oncological outcomes in patients diagnosed with colorectal cancer.MethodsA comprehensive literature search was conducted in PubMed, Embase, and Web of Science to identify eligible studies from inception to September 01, 2024, with an update on December 23, 2024. The primary endpoints evaluated were survival outcomes. Hazard ratios (HRs) with corresponding 95% confidence intervals (CIs) for survival outcomes were either extracted or calculated. A random-effects model was applied to pool all of the results. Statistical analyses were performed using R software, version 4.2.1.ResultsA total of 24 retrospective cohort studies including 9,628 colorectal cancer patients were included. The pooled results demonstrated that patients with higher CONUT score exhibited significantly poorer outcomes across multiple survival metrics: overall survival (HR = 1.73; 95%CI: 1.50–2.01; P < 0.01; I2 = 62%), recurrence-free survival (HR = 1.51; 95% CI: 1.22–1.87; P < 0.01; I2 = 14%), disease-free survival (HR = 1.61; 95% CI: 1.33–1.95; P < 0.01; I2 = 35%), and cancer-specific survival (HR = 3.94; 95% CI: 2.34–6.62; P < 0.01; I2 = 0%). Furthermore, an additional study indicated that the pre-treatment CONUT score may serve as a potential prognostic indicator for progression-free survival in colorectal cancer patients undergoing first-line chemotherapy (P < 0.05).ConclusionOur study demonstrates that the pretreatment CONUT score can serve as a valuable biomarker for predicting long-term oncological outcomes in patients with colorectal cancer.